Application of Electronic Traffic Law Enforcement (E-TLE) Ticketing System Management at Polda West Java - Yuli Indarsih (Enrichment : Journal of Management, 2021)
The West Java Regional Police, starting in 2020, implemented ETLE (Electronic Traffic Law Enforcement) to raise awareness of safety and to reduce the number of traffic violations. ETLE is the digitization of the ticketing process by utilizing technology which is expected to be more efficient and effective throughout the ticketing process as well as assisting the police in administrative management. The method used is descriptive analysis with a normative juridical approach, in which the writer will describe in full the problems that occur in traffic violations and the efforts to overcome them by the police. In this study the authors will use more secondary data, Meanwhile, primary data will be used as a complement to support secondary data in the form of direct interviews with related parties. The research result of the first problem is that E-TLE has the advantage of being faster than conventional ticketing. The advantage is that this system is very practical and fast, in accordance with the principles of a simple, fast and low-cost trial. The application of the E-ticketing system is to facilitate speed and convenience, openness of the ticketing process or as a substitute for the on-site ticketing process